Optimization of KOH etching process for MEMS square diaphragm using response surface method - Norliana Yusof; Badariah Bais; Burhanuddin Yeop Majlis; Norhayati Soin; Jumril Yunas (Institute of Advanced Engineering and Science, 2019)
KOH wet etching is widely used in realizing MEMS diaphragm due to its low cost, safe and easy handling. However, wet etching process parameters need to be studied thoroughly in order to realize the desired shape and size of MEMS devices. This paper presents the numerical study and optimization of KOH etching process parameters using the response surface method (RSM). Face central composite design (FCC) of RSM was employed as the experimental design to analyze the result and generate a mathematical prediction model. From the analysis, the temperature was identified as the most significant process parameter that affects the etching rate, thus affecting the thickness and size of the diaphragm. The results of RSM prediction for optimization were applied in this study. Particularly, 45% of KOH concentration, temperature of 80°C, 1735 µm2 of mask size, and 7.2 hours of etching time were implemented to obtain a square MEMS diaphragm with thickness of 120 µm and size of 1200 µm2. The results of RSM based optimization method for KOH wet etching offers a quick and effective method for realizing a desired MEMS device.